PENGARUH KOMPETENSI, PROFESIONALISME, INDEPENDENSI, OBJEKTIVITAS, DAN PEMBAGIAN TUGAS TERHADAP EFEKTIVITAS PENGAWASAN ALOKASI DANA DESA - Eka Farah Dewi; Agus Sunarmo; Eko Suyono; Permata Ulfah (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
This study aims to determine competency, professionalism, independence, objectivity and division of tasks towards the effectiveness of supervision of village fund allocation. The population in this study were all 61 Inspectorate employees including 1 Inspector, 17 Secretariat, 3 Assistant Inspectors, 8 P2UPD, and 32 Auditors who were registered in the 2017 Government Agency Inspectorate of Banyumas Regency Performance Report. The sample in this study were 43 employees including officials internal supervisor of the Inspectorate of Banyumas Regency. The results of the study show that: (1) Competence influences (significantly) the effectiveness of supervision of village fund allocation, (2) Professionalism has an effect (significantly) on the effectiveness of supervision of village fund allocations, (3) Independence influences (significantly) the effectiveness of village fund allocation monitoring. (4) Objectivity influences (not significant) on the operational performance of cooperatives, (5) Division of tasks influences (significantly) on the effectiveness of supervision of village fund allocations, (6) Competence is not the variable that most influences the effectiveness of supervision of village fund allocation. The implication from the above conclusions were (1) For the government, the effectiveness of supervision of Village Fund Allocation can be increased, among others by: (a) more intense supervision of APIP compliance with its role as an agent in reporting its performance to prinicipal, (b) placing the APIP position appropriately free from intervention and obtaining adequate support from the Regional Government to be able to work with the auditee and carry out work freely and (c) the availability of supporting facilities and infrastructure that can maximize the performance of the Regional Inspectorate in carrying out the supervisory function in Banyumas Regency.(2) For the Inspectorate, the effectiveness of supervision of the Village Fund Allocation can be increased, among others by: (a) involvement in clients sought not to have a working relationship with supervised clients; (b) The Inspectorate holds a continuous mentoring program in the field of soft skills; (c) Maintaining honesty and fairness, impartiality and not having feelings of reluctance.